The Impact of Oral-Gut Inflammation in Cerebral Palsy - Ferreira, Ana Cristina Fernandes Maria; Eveloff, Ryan J.; Freire, Marcelo; Santos, Maria Teresa Botti Rodrigues (Frontiers in Immunology, 2021)
Background: Oral-gut inflammation has an impact on overall health, placing subjects at risk to acquire chronic conditions and infections. Due to neuromotor disturbances, and medication intake, cerebral palsy (CP) subjects present intestinal constipation, impacting their quality of life (QOL), We aimed to investigate how oral inflammatory levels predicted gut phenotypes and response to therapy. Methods: A total of 93 subjects aging from 5-17 years were included in the study, and assigned into one of the 4 groups: CP with constipation (G1, n=30), CP without constipation (G2, n=33), and controls without CP with constipation (G3, n=07) and without CP and without constipation (G4, n=23). In addition to characterizing subjects’ clinical demographics, medication intake, disease severity levels, salivary cytokine levels (TNF-α, interleukin(IL)-1β, IL-6, IL-8, IL-10), and Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD). Statistical significance was evaluated by Shapiro-Wilks, Student’s T-Test, ANOVA, and ANCOVA analysis. Results: Salivary proinflammatory cytokines were highly correlated with the severe form of gut constipation in G1 (P < 0.001), and out of all cytokines IL-1β levels demonstrated highest correlation with all gut constipation (P < 0.05). A significant relationship was found between the type of medication, in which subjects taking Gamma-Aminobutyric Acid (GABA) and GABA+ (GABA in association with other medication) were more likely to be constipated than the other groups (P < 0.01). Cleary salivary inflammatory levels and gut constipation were correlated, and impacted QOL of CP subjects. G1 presented a lower QOL mean score of CPCHILD (49.0 ±13.1) compared to G2 (71.5 ± 16.7), when compared to G3 (88.9 ± 7.5), and G4 (95.5 ±5.0) (P < 0.01). We accounted for gingival bleeding as a cofounder of oral inflammation, and here were no differences among groups regarding gender (P = 0.332) and age (P = 0.292). Conclusions: Collectively, the results suggest that saliva inflammatory levels were linked to gut constipation, and that the clinical impact of medications that controlled gut was reliably monitored via oral cytokine levels, providing reliable and non-invasive information in precision diagnostics.